2011
DOI: 10.1111/j.1398-9995.2011.02721.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing school environments with and without legislation for the prevention and management of anaphylaxis

Abstract: Background School personnel in contact with students with life-threatening allergies often lack necessary supports, creating a potentially dangerous situation. Sabrina’s Law, the first legislation in the world designed to protect such children, requires all Ontario public schools to have a plan to protect children at risk. Though it has captured international attention, the differences a legislative approach makes have not been identified. Our study compared the approaches to anaphylaxis prevention and managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 22 publications
3
40
0
1
Order By: Relevance
“…With the prevalence of food allergy rapidly on the rise, [14][15][16] school districts must be prepared to administer life-saving medication in an environment where contact with food is unavoidable. 6,17,18 Previous research suggests that the cause of an anaphylactic event often goes unrecognized. 13 Similarly, the trigger in more than one third of all events requiring administration of district-issued EAIs was unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…With the prevalence of food allergy rapidly on the rise, [14][15][16] school districts must be prepared to administer life-saving medication in an environment where contact with food is unavoidable. 6,17,18 Previous research suggests that the cause of an anaphylactic event often goes unrecognized. 13 Similarly, the trigger in more than one third of all events requiring administration of district-issued EAIs was unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…These policies are based on the principles of food allergen avoidance, including the avoidance of food sharing and cross-contact, and preparedness with epinephrine. However, previous studies demonstrated that school personnel often lack the knowledge and skills necessary to recognize and treat anaphylactic reactions (12)(13)(14). Many schools did not provide their staff with education on how to prevent allergic reactions or respond to life-threatening events (4,15).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that even in legislated environments, the actual implementation of school anaphylaxis policies has been suboptimal. Meanwhile, school boards in legislated environments have made greater efforts to support students at risk of anaphylaxis compared to non-legislated ones (14). On the other hand, a survey by Wu and Hill (18) found that 53% of schools in Indianapolis had no policy for the management of anaphylaxis and the remaining 47% had a policy that consisted only of calling 911.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations